Detection of HIV-1 infections in blood donors during the pre-seroconversion window period in São Paulo, Brazil - Salles,Nanci Alves (2019)
Abstract By decreasing the pre-seroconversion window period, nucleic acid testing (NAT) has improved the safety of blood products and reduced the risk of transfusion-transmitted infections. Between 2011 and 2017, NAT determinations for approximately 898,202 donations were performed at Fundação Pró-Sangue/Hemocentro de São Paulo (FPS-HSP). Three seronegative HIV-viremic donations were detected. The NAT yield rate per million donations was 3.34 for HIV, and the acute HIV-1 infections detected are described, followed by a brief review of the situation in Brazil.